If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 95 + -3x = 5x + 7 Reorder the terms: 95 + -3x = 7 + 5x Solving 95 + -3x = 7 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 95 + -3x + -5x = 7 + 5x + -5x Combine like terms: -3x + -5x = -8x 95 + -8x = 7 + 5x + -5x Combine like terms: 5x + -5x = 0 95 + -8x = 7 + 0 95 + -8x = 7 Add '-95' to each side of the equation. 95 + -95 + -8x = 7 + -95 Combine like terms: 95 + -95 = 0 0 + -8x = 7 + -95 -8x = 7 + -95 Combine like terms: 7 + -95 = -88 -8x = -88 Divide each side by '-8'. x = 11 Simplifying x = 11
| 2x+14=16-8x | | (4x^2+3x+7)(8x-5)= | | 2x+1.1=4.5 | | -x^3+3x^2+2=0 | | 9x-6=-33 | | 3x^2+15=90 | | (x+2)(2x^2+9x+8)= | | -x^3-3x^2+2=0 | | x^2+20x=12x | | C=4(n+3) | | (x^6+x^4+x^2)(x^2-1)= | | 4.2x-4.02=2.52-6.7x | | 20n-5=25n | | (7x^2-x-5)(2x+8)= | | 12x+24=2x+134 | | (3x^2-2x-7)(9x^2+8x+6)= | | 149-2x=43x+19 | | 2x=8x-30 | | 3-4x=x/3 | | 10-10x=46-31x | | 114-6x=30x+18 | | 125-4x=5x+17 | | 12-9x=164-37x | | (x^2+x+7)(x-9)= | | 12+34+13= | | (4x^2-5x-4)(6x+9)= | | 6x-2=13x-5 | | 2x+7=-63-8x | | 6x-2=13x-24 | | (3x^2+6x+9)(8x-4)= | | x^2-3x=-4 | | 157/527652= |